1987
DOI: 10.1152/ajpregu.1987.253.4.r541
|View full text |Cite
|
Sign up to set email alerts
|

Blood volume restitution after hemorrhage in adult sheep

Abstract: Indirect experimental evidence suggested the possibility that the restoration of blood volume to normal hemorrhage in adult sheep may occur more quickly than in other species that have been studied. To test this hypothesis, we studied unanesthetized chronically catheterized adult female sheep 1-2 wk after splenectomy. An average of 19.6 +/- 1.4% (SE) of their initial blood volume was removed over 10 min. Blood volume restitution at 0.5, 1, 3, 5, 7, 24, and 48 h posthemorrhage averaged 12 +/- 3, 34 +/- 3, 41 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Apparently, the fluid transfer was not facilitated by concomitant hyperglycaemia, as has been suggested from studies in anaesthetized dogs (Knott et al 1969) and cats (Jarhult 1973), since the plasma osmolality remained unchanged during the experiments. This is in accordance with the observations in the same species by Grimes et al (1987), who also found that during the first h following a rapid haemorrhage of 19% of the blood volume, about one third of the removed volume was spontaneously recovered, partly via a recovery of the total plasma protein mass. With regard to this, and the fact that sheep can release substantial amounts of erythrocytes from the spleen (Torrington et al 1989), it is impossible to calculate fluid shifts from changes in plasma protein concentration and haematocrit.…”
Section: Discussionsupporting
confidence: 93%
“…Apparently, the fluid transfer was not facilitated by concomitant hyperglycaemia, as has been suggested from studies in anaesthetized dogs (Knott et al 1969) and cats (Jarhult 1973), since the plasma osmolality remained unchanged during the experiments. This is in accordance with the observations in the same species by Grimes et al (1987), who also found that during the first h following a rapid haemorrhage of 19% of the blood volume, about one third of the removed volume was spontaneously recovered, partly via a recovery of the total plasma protein mass. With regard to this, and the fact that sheep can release substantial amounts of erythrocytes from the spleen (Torrington et al 1989), it is impossible to calculate fluid shifts from changes in plasma protein concentration and haematocrit.…”
Section: Discussionsupporting
confidence: 93%
“…By the external removal or addition of cells to the sampling space, the volume of the sampling space can be estimated under the assumption that the total sampling space volume remains constant. Following an acute phlebotomy (i.e., removal of blood cells) the original blood volume is re-established within 24-48 h if no plasma volume expanders are administered [7,25], therefore the assumption of a constant blood volume (i.e., the sampling space) is reasonable when dealing with populations of blood cells and the 24-48 h lag-time for re-establishment of the blood volume is considered. The original blood volume will be reestablished even more rapidly if plasma or other blood volume expander is administered, due to increased osmotic pressure in the vascular system.…”
Section: Calculation Of the Sampling Space Volumementioning
confidence: 99%
“…The time invariant "point distribution" cellular lifespan model, is obtained by replacing in Eq. 19 the time variant Weibull distribution with a time invariant dirac delta function, δ (ω − a), which upon simplification gives: (25) where:…”
Section: Comparison To Other Lifespan Modelsmentioning
confidence: 99%
“…Information about decreases in blood pressure and/or volume is transmitted to the magnocellular VP and OT neurons in the paraventricular (PVN) and supraoptic nuclei (SON) via the A1 catecholamine pathway, which utilizes ATP and norepinephrine as neurotransmitters (6). Postural changes induce acute elevations in plasma VP (21), while prolonged decreases in blood pressure and/or volume can elicit increases in plasma VP/OT that are sustained for hours to days (3,15,29). The absence of these sustained elevations in plasma VP leads to cardiovascular collapse in hemorrhagic and septic shock (24,27,30).…”
mentioning
confidence: 99%